Wide area monitoring system control management of the IEEE-14 bus system using least square support vector regression - Lilik Jamilatul Awalin; Syahirah Abd Halim; Nor Azuana Ramli; Jafferi Bin Jamaludin; Mohd Syukri Ali (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The wide area monitoring system (WAMS) records and monitors every fault or disturbance that occurs in a power system network using phasor measuring units (PMUs). Extensive monitoring of the condition of the electrical power system can ensure the sustainability of reliable energy. The accuracy of the PMUs placement can be determined using the least square support vector regression (LS-SVR) technique. The primary goal of this study is to assess the level of accuracy of the PMUs placement using mean square error (MSE). First, the IEEE-14 bus system equipped with PMUs was built in Matlab software using Simulink. The MSE of the PMUs was then calculated using the LS-SVR. The results revealed that the lower the MSE, the better the PMUs placement. It was also observed that placing the PMUs on bus 2, bus 6, and bus 9 produced the lowest value of MSE.